Practicing psychotherapy : lessons on helping clients and growing as a professional - Chamberlain, Linda L. (New York, NY : Routledge, 2021)
"In this book of lessons learned from working as a psychotherapist for over 40 years, Dr. Chamberlain shares her varied expertise and experiences, bestowing the wisdom she has gleaned throughout her career from patients, students, teachers, and colleagues. The text examines three core themes: how helping clients is often intertwined with the therapist's own life journey; the experience of building intimate relationships with vulnerable populations; and the process of accepting loss, letting go, and moving forward, both for the client and the therapist. Prioritizing personal narratives, case examples, professional research, and discussions with experienced clinicians, this book marks the significant impact psychotherapy has on not just patients and clients but also the mental health professional. Offering enlightenment for readers ranging from longstanding psychotherapists to former patients, this unique book provides a particularly valuable resource for beginning therapists and therapists-in-training who seek a greater understanding of what it means to be a successful and effective therapist"--
OCLC-licensed vendor bibliographic record.
Keywords: Psychotherapy; Psychotherapists -- Vocational guidance; Psychotherapist and patient; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General